A STUDY ON ANTICANCER ACTIVITY OF CAULIS SPATHOLOBI EXTRACT ON HUMAN OSTEOSARCOMA SAOS-2 CELLS - Liu, Bo; Liu, Jinlan; Chen, Jing; Zhu, Dongmei; Zhou, Huajiang; Wang, Ximing (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the present study was to investigate the anticancer activity of Chinese medicine Caulis Spatholobi extract on multicentric osteosarcoma cells. Ultraviolet spectrophotometry was used to determine the total flavonoid content in each sample; vanillin sulphuric acid assay was used to determine the condensed tannin content in each sample; and the varying degrees of inhibitory activities of ethanol, ethyl acetate and n-butanol extracts of Caulis Spatholobi on human osteosarcoma Saos-2 cells were studied. The results showed that the inhibitory activity of ethyl acetate extract was the highest among the four extracts. The condensed tannin contents of 1.2 mg/mL Caulis Spatholobi water extract, ethanol extract, ethyl acetate extract and petroleum ether extract were 26.23%, 48.36%, 70.18% and 40.51% respectively; and condensed tannin content of 1.5 mg/mL Caulis Spatholobi water extract, ethanol extract, ethyl acetate extract and petroleum ether extract were 4.15%, 5.81%, 8.76% and 7.30% respectively.